Anatomy Behind the Facial Overfilled Syndrome: The Transverse Facial Septum. Issue 8 (August 2020) - Cotofana, Sebastian; Gotkin, Robert H.; Frank, Konstantin; Lachman, Nirusha; Schenck, Thilo L.
Abstract : BACKGROUND: The midface is an area of high demand for minimally invasive cosmetic procedures, that is, soft-tissue filler injections. OBJECTIVE: To investigate the functional anatomy behind the facial overfilled syndrome observed after soft-tissue filler injections. MATERIALS AND METHODS: The clinical part of the study enrolled 25 volunteers (12 men and 13 women, Caucasians); the anatomical part included 72 fresh frozen cephalic specimens obtained from 32 male and 40 female body donors. 3D surface scanning procedures were applied to calculate the maximal anterior projection of the midface. RESULTS: Upon smiling, the point of maximal anterior projection shifted cranially in men by 12.43 ± 8.8 mm (difference between resting and smiling; p < .001) and by 8.75 ± 4.1 mm in women ( p < .001). Cadaveric dissections identified a septum originated from the underside of the zygomaticus major muscle forming a transversely running boundary between the buccal space and the deep midfacial fat compartments. CONCLUSION: Facial overfilled syndrome can potentially be explained by the presence of the transverse facial septum. Dynamic filling—injecting small amounts of filler and asking the patient to smile repeatedly during the procedure—seems to be a viable way to avoid this adverse event during soft-tissue filler injection.